PENGARUH PEMBERIAN LAYANAN INFORMASI UNTUK MENCEGAH PROKRASTINASI AKADEMIK PADA SISWA - Pikri Nopen; Hadiwinarto; Rita Sinthia (UNIVERSITAS BENGKULU, 2023)
This study aims to determine whether there is an effect of providing information services to reduce academic procrastination in sma negeri 04 kaur students and is motivated by researcher observations and interviews with guidance and counseling teachers at sma negeri 04 kaur. The method used in this research is one-group pre-test and post-test design. the population in this study was the entire xi ipa class and the sample of this study was xi ipa 1 class students totaling 32 people. determination of the sample using purposive sampling technique. data were obtained from an academic procrastination questionnaire with a likert scale. the results of the calculation of the average score of the level of academic procrastination in students before being given information services were 114 and decreased after being given information services with an average score of 85. the results of hypothesis testing with the t test are 8,629 with a sig. (2-tailed) value of 0.000 so that the sig. (2-tailed) value <0.05 which means ho is rejected and ha is accepted. based on these results, it can be concluded that there is an effect of providing information services to reduce academic procrastination in students. Keywords: information service, academic procrastination, students